RNA polymerase subunit homology among cyanobacteria, other eubacteria and archaebacteria. - Schneider, G J (1988)
RNA polymerase purified from vegetative cells of the cyanobacterium Anabaena sp. strain PCC 7120 contains a dissociable sigma factor and a core of five subunits: the beta', beta, and two alpha subunits characteristic of all eubacteria and an additional 66,000-molecular-weight polypeptide called gamma. Fifteen of fifteen strains of unicellular and filamentous cyanobacteria tested contained a serologically related gamma protein. Antiserum to gamma reacted with Escherichia coli beta' and the A subunit of RNA polymerase of the archaebacterium Sulfolobus acidocaldarius. Thus the evolution of the RNA polymerase beta' subunit has followed different paths in three groups of procaryotes: cyanobacteria, other eubacteria, and archaebacteria.